Consumption Behavior of Students of Sunan Kalijogo Jabung Islamic Boarding School on Syariah Fashion Products (Reviewed in the Maqashid Syariah Approach) - Yusuf Wijaya, Mohammad (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Introduction: The aim of this research is to determine the consumption behavior of female students, what factors influence the consumer behavior of female students and an overview of Islamic economics at the Sunan Kalijogo Islamic Boarding School, Malang. Methods: The research method is qualitative field research, at the Sunan Kalijogo Jabung Islamic Boarding School, Malang Regency. The data source in this research was 10 female students from dormitory D. Results: Factors that influence female students at the Sunan Kalijogo Islamic Boarding School to behave consumptive towards current fashion trends because they are based on self-concept, which is driven more by factors of need and benefit. Meanwhile, external factors that influence students' consumptive behavior are advertising and the information they obtain about fashion. The consumption behavior of students at the Sunan Kalijogo Islamic Boarding School in Malang is in accordance with the rationality of Muslim consumers and in accordance with maqashid sharia. Conclusion and suggestion: The consumption behavior of female students of Sunan Kalijogo Islamic Boarding School in Malang on sharia fashion products has been in accordance with the concept and principles of maqashid sharia, namely in consuming sharia fashion products, students are more oriented and consider aspects of needs, benefits and maslahah, not just desires. The advice that can be given is that the Sunan Kalijogo Malang Islamic Boarding School should maintain the principles that have been held by students to buy goods by looking at their needs and benefits and increase education for students so that they are not easily persuaded by advertisements.